Comparison of the surgical and post-operative outcomes between single incision laparoscopic appendicectomy (cross triangulation method) with normal conventional laparoscopic appendicectomy - Paulraj, Pratheep Samraj Rajendran; Chirayil, Kiran Kailas; Bellasindhi, Renuka Jayakumar; Oli, Punitha Thetraravu; Mathew, Mohith; Jomy, Anish (International Surgery Journal, 2021)
Background: The usual multiport conventional laparoscopic surgeries (appendicectomy) are now being replaced by single incision laparoscopic surgeries (appendicectomy).In our study various aspects of SILS in comparison with the multiport conventional laparoscopic appendicectomy such as incision site pain, duration of surgery, morbidity and instruments used are discussed, duration of surgery, morbidity and instruments used are discussed. Methods: A single blinded randomized control trial was done on patients presenting with acute appendicitis. Pain numerical scale, use of analgesics, time to return to routine activities, hospital re-admission, complication like port site infection, hernia, intra operative complications rates, conversion rates and duration of surgery were evaluated. Various statistics of pain and other parameters are studied and evaluated. The mean operation time, mean recovery time, post-operative pain were statistically analysed using unpaired t-test. Results: Mean operating time was 44.16 minutes for SILS and 26.88 minutes for laparoscopic appendicectomy. The mean operative pain in scale of 1 to 4 was 1.40 and 0.40 for SILS and for laparoscopic appendicenctomy respectively making SILS more pain free and comfortable for the patient. The mean post-operative recovery time was 3.12 days for SILS and 7.88 days for laparoscopic appendicenctomy giving SILS patients more rapid recovery and resumption of work. Conclusions: SILS offers better cosmetic outcome, lesser post-operative pain and shorter duration of hospital stay compared to classical 3 port conventional laparoscopic surgery but at the expense of time. Operative difficulties along with time constraint need to be overcome by the surgeon.